Pengaruh Terapi Guide Imagery Terhadap Penurunan Kecemasan Remaja Korban Bullying Di SMPS Shabilla - Indah Nur Jannah (STIKes Ibnu Sina Ajibarang, 2023)
Bullying has a negative impact not only on victims but also on perpetrators, bullying causes psychological problems for adolescents such as anxiety, they can experience mental and social problems, including suicide. The World Health Organization (WHO) (2020) reveals generically that one of the mental disorders that can occur due to bullying is an anxiety disorder whose directed effect is depression, therapy guide imgery is a therapeutic activity for young victims of bullying who experience anxiety so that it gives the effect of feeling comfortable and relaxes the body. Objective: This study aims to determine the effect of guided imagery therapy on reducing anxiety in adolescent victims of bullying at Shabilla Junior High School. Methods: This type of research is a quantitative study with a Quasi Experimental design with a One group Pre-Post Test Design Group Without Control Design approach and data analysis using the Paired t- Test and Total Sampling method, with a sample of 20 adolescents. Results: The results of the study found that the level of anxiety before being given guide imagery therapy found that most of the teenagers who were victims of bullying had mild anxiety levels, namely as many as 14 teenagers (70%). The level of anxiety of adolescent bullying victims after guided imagery therapy was found that most of the adolescent victims of bullying were at a normal level (not anxious) as many as 12 teenagers (60%), The results of the analysis test found that there was an effect of guided imagery therapy on reducing anxiety in adolescent victims of bullying at Shabilla Junior High School, p value = 0.000 (p < 0.05). Suggestion: Suggestion: for SMPS Shabilla schools to form and deploy an Anti Bullying task force, put up Anti Bullying posters, and specifically for BK (counseling) teachers must be able to master imagery therapy guides for adolescent bullying victims who experience anxiety